A Responsive Communitarianism Development in Bang Rak District, Bangkok - Lertthanakulvat, Suvit; Sonsuphap, Asst.Prof.Dr.Rattaphong (Journal of Dhamma for Life, 2023)
This study aims to: Investigate the development of urban communities in the dimension of community responsibility, examine the self-reliance process in the participatory development of urban communities in the Bang Rak district, Bangkok, and explore community development models for inclusive self-reliance in the urban context of the Bang Rak district, Bangkok, utilizing qualitative research methods, case study techniques, and data collection through document analysis and in-depth interviews with 23 participants. Study Findings indicate that variation in Self-Reliance Levels: Within the Bang Rak area, prototype urban communities exhibited differing levels of self-reliance. The Wat Mueang Kamasthirdharn Community showcased a high degree of community responsibility, social and cultural development, technological advancement, and economic self-sufficiency, while the Phiphak Community, though self-reliant in certain dimensions such as mental well-being and social aspects, faced economic challenges. Community Development Process in Bang Rak as follow: Identifying and Seeking Trustworthy Community Leaders, forming Community Committees as Drivers of Main Activities, communicating Benefits and Necessity of Group Activities, fostering Inclusiveness and Assigning Responsibilities to Community Members, delivering the Benefits of Participation, and lastly establishing Relationships and Communication with External Organizations. Community Development Models: The study reveals distinct business and social enterprise concepts for community development that align with the characteristics, strengths, and unique capabilities of each community. In conclusion, this research provides insights into the heterogeneous levels of self-reliance in urban communities, the processes integral to community development, and the suitability of diverse business and social enterprise models for community sustainability within the Bang Rak district in Bangkok.